Analysis of “Wikiproducers” as future leaders - Arce, Guillermo; Claudio-Quiroga, Gloria (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The profile of consumers and future business leaders is beginning to resemble that of producers and personal digital marketers. The aim is to find out to what extent current education matches the expectations of Wikiproducers and to determine the relationship between the attitudes of these leaders and the businesses of the future. It is a qualitative study through focus groups with university students and in-depth interviews with senior business managers. Among the results is the perception that higher education does not respond to the adaptation needs of the labour market.